Community gate keepers' awareness and perception of prevention of mother-to-child transmission of HIV services in Ibadan, Nigeria (2007)
Each year, around half a million children aged under 15 become infected with HIV and more than 90% are the result of mother-to-child transrnission. Services to prevent mother-to-child HIV transmission (PMTCT) are therefore important entry points for HIV AIDS Prevention, treatment and care services for women, their children and families. The study aimed at identifying level of awareness and knowledge of PMTCT services that can be utilized in improving access. The methodology consisted of 20 individual in-depth interviews spread over Adabeji, Adeoyo/Agbadagbudu, Jakiru/Onipasan and Eleta communities, in Ibadan among household heads, religious and community based leaders. Key factors identified were low knowledge of mother to child transmission, lack of knowledge of the PMTCT services, inadequate community sensitization, inadequate health care facilities. The success of PMTCT programmes demands a shift towards a more community-based approach which calls for strong advocacy, enlightenment and community mobilization for improved awareness and utilization of PMTCT services